1, 2-Dichloroethane Induces Reproductive Toxicity Mediated by the CREM/CREB Signaling Pathway in Male NIH Swiss Mice. (30th August 2017) - Zhang, Yating; Li, Guoliang; Zhong, Yizhou; Huang, Manqi; Wu, Jiejiao; Zheng, Jiewei; Rong, Weifeng; Zeng, Lihai; Yin, Xiao; Lu, Fengrong; Xie, Zhiwei; Xu, Dandan; et al.
Abstract: 1, 2-Dichloroethane (1, 2-DCE) is a widely used chlorinated organic toxicant but little is known about the reproductive disorders induced by its excessive exposure. To reveal 1, 2-DCE-induced male reproductive toxicity and to elucidate the underlying mechanisms, we exposed male National Institutes of Health Swiss mice to 1, 2-DCE by inhalation at 0, 100, 350, and 700 mg/m 3 for 6 h/day, for 1 and 4 weeks. Our findings showed a significant decrease in body weight with increased testis/body weight ratio, reduced sperm concentration and induced malformation of spermatozoa, and vacuolar degeneration of germ cells in the seminiferous tubules of testes in mice exposed to 1, 2-DCE. Cyclic adenosine monophosphate (cAMP)-response element binding protein (CREB) and cAMP-response element modulator (CREM) were significantly inhibited by 1, 2-DCE. This is consistent with the declines in the transducer of regulated CREB activity 1 and activator of CREM in testis, which results in the decrease in lactate dehydrogenase C and testis-specific kinase 1 in the testes. Moreover, the activation of p53 and Bax with the inhibition of Bcl-2 might be the reason for the upregulation of caspase-3 in the apoptosis, as detected by TdT-mediated dUTP nick-end labeling assay in the testes induced by 1, 2-DCE. Finally, elevated testosterone levels were found along with increased levels of gonadotropin-releasing hormone, cAMP, luteinizing hormone (LH), and LH receptors in the testes. These findings suggest that 1, 2-DCE inhibits CREM/CREB signaling cascade and subsequently induces apoptosis associated with p53 activation and mitochondrial dysfunction. This also results in induced malformation of spermatozoa, reduced sperm concentration, and pathological impairment of the testes.